Fluorine-18 click radiosynthesis and microPET/CT evaluation of a small peptide-a potential PET probe for carbonic anhydrase IX. Issue 5 (1st March 2019) - Jia, Lina; Li, Xiao; Cheng, Dengfeng; Zhang, Lan
Graphical abstract: Abstract: Carbonic anhydrase IX (CA IX) is the first carbonic anhydrase found to be associated with cancer that is over-expressed in a variety of human solid tumors. As a surrogate marker for hypoxia, the expression of CA IX is strongly upregulated in hypoxic tumors by hypoxia and hypoxia-inducible factor 1a (HIF-1a). In our pursuit of a CA IX-specific PET probe, we designed and synthesized a peptide-based CA IX imaging probe by the efficient click reaction of 1, 3-dipolar cycloaddition of terminal alkynes and organic azides. The probe 18 F-CA IX-P1-4-10 was obtained with a radiochemical yield of 35–45% (n = 5) and radiochemical purity of >99% in 70–80 min (HPLC purification time included). 18 F-CA IX-P1-4-10 had good stability in phosphate buffered saline (PBS), but about 51% peptide degradation was detected in new-born calf serum (NBCS) after incubation. Preliminary microPET/CT experiments demonstrated a specific uptake of 18 F-CA IX-P1-4-10 in HT29 tumor and the uptake of 18 F-CA IX-P1-4-10 was blocked by peptide CA IX-P1-4-10-Yne pretreatment. Immunohistochemical staining and western blotting studies confirmed the HT29 tumor was CA IX-positive which further proved tumor accumulation of 18 F-CA IX-P1-4-10 was correlated with CA IX expression. The results suggest that 18 F-CA IX-P1-4-10 is a promising PET tracer for the specific imaging of CA IX-expressing tumors at the molecular level.